Genomic Consequences of and Demographic Response to Pervasive Hybridization Over Time in Climate-Sensitive Pikas. (23rd December 2022) - Ge, Deyan; Wen, Zhixin; Feijó, Anderson; Lissovsky, Andrey; Zhang, Wei; Cheng, Jilong; Yan, Chaochao; She, Huishang; Zhang, Dezhi; Cheng, Yalin; Lu, Liang; Wu, Xinlai; et al.
Abstract: Rare and geographically restricted species may be vulnerable to genetic effects from inbreeding depression in small populations or from genetic swamping through hybridization with common species, but a third possibility is that selective gene flow can restore fitness (genetic rescue). Climate-sensitive pikas ( Ochotona spp.) of the Qinghai–Tibetan Plateau (QHTP) and its vicinity have been reduced to residual populations through the movement of climatic zones during the Pleistocene and recent anthropogenic disturbance, whereas the plateau pika ( O . curzoniae ) remains common. Population-level whole-genome sequencing ( n = 142) of six closely related species in the subgenus Ochotona revealed several phases of ancient introgression, lineage replacement, and bidirectional introgression. The strength of gene flow was the greatest from the dominant O . curzoniae to ecologically distinct species in areas peripheral to the QHTP. Genetic analyses were consistent with environmental reconstructions of past population movements. Recurrent periods of introgression throughout the Pleistocene revealed an increase in genetic variation at first but subsequent loss of genetic variation in later phases. Enhanced dispersion of introgressed genomic regions apparently contributed to demographic recovery in three peripheral species that underwent range shifts following climate oscillations on the QHTP, although it failed to drive recovery of northeastern O . dauurica and geographically isolated O . sikimaria . Our findings highlight differences in timescale and environmental background to determine the consequence of hybridization and the unique role of the QHTP in conserving key evolutionary processes of sky island species.